0527 ROLE OF SPOUSE IN CPAP ADHERENCE - Batool-Anwar, S; Baldwin, CM; Fass, S; Goodwin, JL; Kushida, CA; Nichols, D; Quan, SF (Sleep (New York, N.Y.), 2017)
Abstract Introduction: Continuous positive airway pressure (CPAP) adherence among patients with obstructive sleep apnea (OSA) remains suboptimal. This study determined whether marital quality and spouse involvement affects adherence with CPAP therapy, and whether it differs by gender. Methods: 194 subjects recruited from Apnea Positive Pressure Long Term Efficacy Study (APPLES) completed the Dyadic Adjustment Scale (DAS) 3 years after the study. The majority of participants were Caucasian men (84% and 74% respectively), with mean age of 56 years mean BMI of 31 kg/m2, and 62% had severe OSA. Inclusion required that subjects were married during APPLES and still married at the time of DAS administration. The DAS is a validated 32-item self-report instrument measuring marital dyadic consensus, satisfaction, cohesion, and affectional expression. Additionally, questions related to spouse involvement with general health and CPAP use were asked. CPAP compliance was defined as usage documented by device download ≥ 4 h/night. Results: Overall marital quality between the compliant and noncompliant subjects was not different; however, spousal involvement was associated with increased CPAP adherence at 6 months (p=0.01). Gender stratification demonstrated significance only among males (p=0.03). Three years after completing APPLES, 82 participants were still compliant by self-report. At this time point, spousal involvement was not associated with CPAP compliance even after gender stratification. Conclusion: Wife support of husband’s general health, but not husband’s support of wife’s general health is important in determining CPAP compliance in the first 6 months after initiation of therapy, but is not predictive of longer-term adherence. In contrast, marital quality measures were not an important factor in CPAP compliance in this study. This finding for dyadic support by wives, but not husbands is consistent with prior DAS studies. Involvement of both husbands and wives should be considered an integral part of CPAP initiation procedures. Support (If Any): Support (optional): HL068060.